2018
DOI: 10.26550/311/33-41
|View full text |Cite
|
Sign up to set email alerts
|

Recommended practices for the management of surgical smoke and bio-aerosols for perioperative nurses in Thailand

Abstract: Recommended practices for the management of surgical smoke Recommended practices for the management of surgical smoke and bio-aerosols for perioperative nurses in Thailand and bio-aerosols for perioperative nurses in Thailand Usavadee Asdornwised

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…High-filtration surgical masks, designed to filter particulate matter to 0.1 μm, are recommended to filter residual plumes. These masks should be used as an adjunct, not in lieu, of a smoke evacuation device (Asdornwised et al, 2018). Dobrogowski et al (2015) reported that, although the health risk from exposure to surgical smoke during minimally invasive surgical procedures revealed low concentrations of harmful chemical substances, specialized masks and smoke evacuators are still recommended because of chronic exposure that potentially poses a health risk over time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…High-filtration surgical masks, designed to filter particulate matter to 0.1 μm, are recommended to filter residual plumes. These masks should be used as an adjunct, not in lieu, of a smoke evacuation device (Asdornwised et al, 2018). Dobrogowski et al (2015) reported that, although the health risk from exposure to surgical smoke during minimally invasive surgical procedures revealed low concentrations of harmful chemical substances, specialized masks and smoke evacuators are still recommended because of chronic exposure that potentially poses a health risk over time.…”
Section: Literature Reviewmentioning
confidence: 99%